Associations of Gut Microbiota With Heat Stress-Induced Changes of Growth, Fat Deposition, Intestinal Morphology, and Antioxidant Capacity in Ducks - He, Jun; He, Yuxin; Pan, Daodong; Cao, Jinxuan; Sun, Yangying; Zeng, Xiaoqun (Frontiers in Microbiology, 2019)
Accumulating evidence has revealed the dysbiosis of gut/fecal microbiota induced by heat stress (HS) in mammals and poultry. However, the effects of HS on microbiota communities in different intestinal segments of Cherry-Valley ducks (a widely-used meat-type breed) and their potential associations with growth performances, fat deposition, intestinal morphology and antioxidant capacity have not been well evaluated yet. In this study, room temperature of 25 °C was considered as control, and room temperature at 32 °C for 8 h per day was set as the HS treatment. After 3 weeks, the intestinal contents of jejunum, ileum and cecum were harvested to investigate the microbiota composition variations by 16S ribosomal RNA amplicon sequencing. And the weight gain, adipose indices, intestinal morphology and a certain number of serum biochemical parameters were also measured and analyzed. The results showed the microbial species at different levels differentially enriched in duck jejunum and cecum under HS, while no significant data were observed in ileum. HS also caused the intestinal morphological changes (villus height and the ratio of villus height to crypt depth) and the reductions of growth speed (daily gain), levels of serum triglyceride and total cholesterol, and antioxidant activity (higher malondialdehyde content and lower total antioxidant). The higher abdominal fat content and serum glucose level were also observed in HS ducks. The Spearman correlation analysis indicated that in jejunum the phyla Firmicutes and Proteobacteria were associated with average daily gain, feed/gain, serum triglyceride and malondialdehyde levels, and villus height/crypt depth (P < 0.05). The phylum Firmicutes and genus Acinetobacter were significantly associated with fat deposition and serum glucose level (P < 0.05). The genus Lactobacillus was positively associated with serum total antioxidant (P < 0.05), while some other microbial species were found negatively associated, including order Pseudomonadales, genera Acinetobacter and unidentified_Mitochondria. However, no significant correlations were observed in cecum. These findings imply the potential roles of duck gut microbiota in the intestinal injuries, fat deposition and reductions of growth speed and antioxidant capacity caused by HS, although the molecular mechanisms requires further investigation.